In Convent Walls : The Story of the Despensers - Holt, Emily Sarah, 1836-1893; Irwin, M. (Madelaine) (Salt Lake City, UT : Project Gutenberg, 2009)
"In Convent Walls" by Emily Sarah Holt is a historical novel written in the late 19th century. The story begins with Dame Cicely de Chaucombe, who recounts her experiences and observations while serving in the household of Queen Isabel of France during the 14th century, particularly her reflections on the queen's ambition and its dark consequences. The book explores themes of moral choices, personal sacrifice, and the ramifications of ambition, placing the characters' decisions against the backdrop of historical events. The opening of the novel sets the stage for Cicely's narrative, employing a conversational and reflective tone that draws readers into her world. Cicely's initial hesitations about writing her story reveal her character's depth, as she is both observant and critical of those in power, including Queen Isabel and the men surrounding her. Through dialogues with her husband Jack and reflections on historical figures like Sir Roger de Mortimer, the narrative hints at impending conflict and intrigue within the royal court. This opening portion lays the groundwork for Cicely's personal journey within a broader historical context, inviting readers to witness not only the challenges she faces but also the moral dilemmas presented by those in positions of influence and ambition. (This is an automatically generated summary.)
Release date is 2009-02-01
Produced by Nick Hodson of London, England
Keywords: Historical fiction; Great Britain -- History -- Edward II, 1307-1327 -- Fiction